Understanding, anticipating and managing health risks linked to climate migration - François Gemenne (Field Actions Science Reports)
In this interview, François Gemenne discusses the specific challenges facing climate refugees, who are often wrongly differentiated from economic refugees. These migration movements are driven by sudden disasters (storms, floods, etc.) and incremental changes (rising sea levels, soil impoverishment, etc.) that are heightening the vulnerability of certain regions. Health problems, whether physical or mental, are omnipresent at every stage of these refugees' journeys – all the more when they are women – from the moment the disaster strikes to when they arrive in a new host country.Constructing policies to adapt to and manage these new flows requires taking account of a number of subjective factors. People’s perceptions of the effects of climate change often have a greater influence on their choice to leave than objective reality. Health, associated with push factors that encourage people to leave, such as the appearance of new diseases, and pull factors that draw refugees toward certain locations, such as access to healthcare, is embedded in a complex web of factors behind the decision to leave. Given this reality, countries can decide to consider and organize these flows in terms of an adaptation strategy, instead of a failure to adapt. Migration can improve the health and security of refugees, but also more broadly the health and security of people in host and home countries.